The Malaysian Music Therapists: Their Careers, Challenges, and the Future - Wang I Ta,; Beh Wen Fen, (Wacana Seni Journal of Arts Discourse, 2024)
In the West, music therapy has emerged since the mid-twentieth century and has been recognised as a formal profession promoted in both clinical and educational settings. It encompasses cognitive, behavioural, psychiatric, psychosocial, and neurological domains. However, compared to its robust development in the West and neighbouring countries, the profession in Malaysia is at the developing stage. To the best of the researcher’s knowledge, no studies have investigated the causes from the perspectives of Malaysian music therapists. The current research invited five practising music therapists for semi-structured interviews. Through the interpretative phenomenological analysis (IPA), the following themes emerged to reflect the status quo of the profession: (1) career intention and realisation, (2) awareness and acceptance of the public, and (3) the status of the advocacy. It showed that Malaysian music therapists intended to work in healthcare. Although the recent advocacy effort has focused on making music therapy under allied health, it is not included in the clinical setting. The study concluded that awareness still needs to be raised among clinical stakeholders, the government, and the public. There should be more clinical research collaboration to generate local data to promote the profession under allied health, encourage more local training programmes, and elevate awareness and acceptance among the public and the government.